The Paris Project - Gephart, Donna (Simon & Schuster Books for Young Readers, 2019)
Cleveland Rosebud Potts yearns to leave Sassafras, Florida for a rich and cultured life at The American School of Paris, but problems with family, friends, and finances stand in her way.